Simulation of the influence of external factors on the level of use of the regional tourism potential: A practical aspect - Nestor Shpak; Oksana Muzychenko-Kozlovska; Maryana Gvozd; Włodzimierz Sroka (Administrative Sciences, 2021)
Today, the issue of development of the tourism industry is becoming increasingly relevant, as this industry is an important component of the economic system of each country. External factors have the most significant impact on the development of tourism: natural disasters, wars, economic crises, and pandemics have had a destabilizing effect on the development of the tourism industry around the world. To avoid or reduce the impact of negative phenomena on the tourism industry of a particular country or region, it is crucial to predict the impact of external factors, identify the most important of them, and develop strategic measures to turn threats into opportunities. In the context of solving the mentioned problem, this study aims to model the impact of external factors on the level of use of tourism potential of the region. After all, tourist services and products of each country and region are unique, as they are formed under the influence of existing special natural resources, cultural heritage, environmental, social and other factors inherent only in them; and if in one country/region the influence of a certain factor can weaken the development of tourism, in another one - it can stimulate it. A method of comparison with the reference value and a method of calculating the integral indicator were used in the study. Based on the analysis, an integral indicator of the level of use of the tourist potential of the region was calculated and the method of assessing the impact of external factors on the level of tourist potential on the example of the Carpathian region of Ukraine was tested.
Keywords: 350; external factors; integral integrated method; region; tourism potential; tourism resources; tourism sector